برنامج تدريبي قائم على بعض مهارات التفكير الإيجابي في تنمية مفهوم الذات لطلاب كلية التربية العجيلات - المنصر، فوزي محمد علي (الجمعية الليبية لعلوم التعليم, 2023)
هدفت الدراسة الحالية إلى معرفة فاعلية برنامج تدريبي قائم على بعض مهارات التفكير الإيجابي في تنمية مفهوم الذات لدى طلاب كلية التربية، وتكونت عينة الدراسة من(50) طالبا وطالبة من طلاب كلية التربية العجلات جامعة الزاوية تراوحت أعمارهم من )21-22) عاما، وقد تم تقسيمهم إلى مجموعتين: الأولى تجريبية تكونت من (25) طالبا وطالبة، والثانية ضابطة تكونت من (25) طالبا وطالبة. وتم تطبيق مقياس مفهوم الذات، وبرنامج تدريبي قائم على بعض مهارات التفكير الإيجابي. وأسفرت الدراسة عن وجود فروق ذات دلالة إحصائية بين متوسطات درجات طلاب المجموعة التجريبية في القياس القبلي والبعدي لصالح البعدي. عدم وجود فروق ذات دلالة إحصائية بين متوسطات درجات طلاب المجموعة التجريبية للقياسين البعدي والتتبعي بعد الانتهاء من تطبيق البرنامج بشهرين. وجود فروق ذات دلالة إحصائية بين متوسطات درجات طلاب المجموعة التجريبية ومتوسطات درجات طلاب المجموعة الضابطة في مفهوم الذات في القياس البعدي لصالح المجموعة التجريبية. The present study aimed to verify the effectiveness of training on some positive thinking skills for developing the self concept among the faculty of education students. The study sample consisted of (50) students (males and females) from faculty of education students at University in Al Zawiya, in age between (21- 22) years old. The basic study sample of education faculty students was divided into two groups: The experimental group: It consisted of (25) students (males and females), and the control group: It consisted of (25) students (males and females). The study tools included the training program based on positive thinking skills. The self concept scale. The results of the study are: There are statistically significant differences between the mean scores of the experimental group students in the pre and post measurements in favor of the post. There aren't statistically significant differences between the mean scores of the experimental group students for the post and follow-up measurements two months after the completion of the program. (3) There are statistically significant differences between the mean scores of the experimental and control group students in both self concept in the post measurement in favor of the experimental group.
Keywords: علم النفس الإيجابي -- التفكير الإيجابي -- طلبة الجامعات -- البرامج التدريبية